An Individual Participant Data Population Pharmacokinetic Meta-analysis of Drug-Drug Interactions between Lumefantrine and Commonly Used Antiretroviral Treatment - Francis, Jose; Barnes, Karen I.; Workman, Lesley; Kredo, Tamara; Vestergaard, Lasse S.; Hoglund, Richard M.; Byakika-Kibwika, Pauline; Lamorde, Mohammed; Walimbwa, Stephen I.; Chijioke-Nwauche, Ifeyinwa; Sutherland, Colin J.; Merry, Concepta; et al. (Antimicrobial agents and chemotherapy, 2020)
Treating malaria in HIV-coinfected individuals should consider potential drug-drug interactions. Artemether-lumefantrine is the most widely recommended treatment for uncomplicated malaria globally. Lumefantrine is metabolized by CYP3A4, an enzyme that commonly used antiretrovirals often induce or inhibit. A population pharmacokinetic meta-analysis was conducted using individual participant data from 10 studies with 6,100 lumefantrine concentrations from 793 nonpregnant adult participants (41% HIV-malaria-coinfected, 36% malaria-infected, 20% HIV-infected, and 3% healthy volunteers). Lumefantrine exposure increased 3.4-fold with coadministration of lopinavirritonavir- based antiretroviral therapy (ART), while it decreased by 47% with efavirenzbased ART and by 59% in the patients with rifampin-based antituberculosis treatment. Nevirapine- or dolutegravir-based ART and malaria or HIV infection were not associated with significant effects. Monte Carlo simulations showed that those on concomitant efavirenz or rifampin have 49% and 80% probability of day 7 concentrations 200 ng/ml, respectively, a threshold associated with an increased risk of treatment failure. The risk of achieving subtherapeutic concentrations increases with larger body weight. An extended 5-day and 6-day artemether-lumefantrine regimen is predicted to overcome these drug-drug interactions with efavirenz and rifampin, respectively.
Keywords: Uncomplicated malaria; Lumefantrine; Human immunodeficiency virus; Drug-drug interactions; Population pharmacokinetics